The Influence of Training and Work Compensation on Employee Performance Through Competence as a Mediating Variable: JEL Classification: M12, M53, J24, J31, O15 - Herwanto, Fadjar Nugraha; Hartono, Edy; Kartono, Kartono (Journal La Bisecoman, 2025)
Competition in the engineering services industry demands that companies have competent, productive, and adaptable human resources to technological developments. PT Wijaya Anugrah Persada Raya (WAPR), a company engaged in engineering services and supply, strives to improve employee performance through appropriate training and compensation. However, the effectiveness of these two factors in improving performance still needs to be studied, particularly considering the role of competency as a mediating variable. This study aims to analyze the effect of training and compensation on employee performance through competency as a mediating variable. The approach used was quantitative, using the Partial Least Square–Structural Equation Modeling (PLS–SEM) method. Data were collected through an online questionnaire, with respondents being PT WAPR employees. The results showed that job training significantly impacted employee performance, while compensation had no direct effect. Training and compensation had a positive effect on competency, but competency did not significantly mediate their influence on performance. These findings confirm that performance improvement is not solely determined by training and compensation but is also influenced by other factors such as motivation, work environment, and job satisfaction.